Assessment of household water treatment and storage practices - Pradhan, Subrat K.; Sinha, Upasana; Satapathy, Durga M.; Swain, Amit P.; Mishra, Rudra P. (International Journal Of Community Medicine And Public Health, 2018)
Background: Maintenance of drinking-water quality is a pillar of primary prevention and continues to be the foundation for the prevention and control of waterborne diseases. Improved water supply and sanitation, and better management of water resources, can boost countries’ economic growth and can contribute greatly to poverty reduction. The objective of the study was to assess household water treatment and safe storage (HWTS) practice. Methods: A cross-sectional study was conducted for a period of 2 months. Total of 250 household were surveyed under the UHTC. Data was collected using WHO toolkit for monitoring and evaluating household water treatment and safe storage programme. Descriptive analysis was done. Results: Majority had piped connection (32%) followed by public standpipe (31.2%), hand pump (27.6%) as source of water. 60% had knowledge about boiling followed by chlorination 27%, membrane filters 22.4%. Majority i.e. 63% of the participants had thought boiling as the best method for disinfection of drinking water. Conclusions: Majority had piped connection, Maximum kept water container clean and covered. Only one fourth of the total household surveyed suffered from diarrhea in last 6 months.